Proteomics - Palzkill, Timothy (Boston, MA : Springer US, 2002)
Proteomics is an introduction to the exciting new field of proteomics, an interdisciplinary science that includes biology, bioinformatics, and protein chemistry. The purpose of this book is to provide the active researcher with an overview of the types of questions being addressed in proteomics studies and the technologies used to address those questions. Key subjects covered in this book include: an assessment of the limitations of this approach and outlines new developments in mass spectrometry that will advance future research high-throughput recombinant DNA cloning methods used to systematically clone all of the open reading frames of an organism into plasmid vectors for large scale protein expression and functional studies such as protein-protein interactions with the two-hybrid system protein structure an overview of large-scale experimental attempts to determine the three-dimensional structures of representative sets of proteins computational approaches to determining the three-dimensional structure of proteins. Proteomics provides a starting point for researchers who would like a theoretical understanding of the new technologies in the field, and obtain a solid grasp of the fundamentals before integrating new tools into their experiments. Written with attention to detail, but without being overwhelmingly technical, Proteomics is a user-friendly guide needed by most biologists today.
Protein Identification and Analysis -- Protein Expression Mapping -- High-Throughput Cloning of Open Reading Frames -- Protein-Protein Interaction Mapping: Experimental -- Protein-Protein Interaction Mapping: Computational -- Protein Arrays and Protein Chips -- Conclusions.
Elektronická reprodukce.
Keywords: genetika člověka; biochemie; proteomika; human genetics; biochemistry; proteomics; e-knihy online; e-books online